Evaluasi Tingkat Bahaya Erosi Beberapa Penggunaan Lahan di Kecamatan Sidoharjo, Wonogiri, Jawa Tengah dengan Metode USLE (Universal Soil Loss Equation) - Aktavia Herawati; Sutarno Sutarno; Mujiyo Mujiyo; Yogi Sukma Mahendra (Pedontropika : Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2022)
Erosion is one of the problems in agricultural activities. Soil erosion can cause loss of topsoil that contains nutrients for plants. The diversity of land use in agricultural activities affects the amount of erosion that occurs. This research aims to identify the level of erosion hazard in several agriculture land use and the determine factor of erosion, as well as provide direction for conservation in Sidoharjo District, Wonogiri, Central Java. This research is a survey research with exploratory descriptive approach based on the results of field observation and laboratory analysis. Sampling points were determined purposively on 12 land units. Parameters observed were soil texture, soil structure, organic matter, permeability, slope length and slope, vegetation, and conservation management. The results showed that the level of erosion hazard in the study area contained light, moderate, and severe erosion hazard levels, and moorland have the highest level and paddy field have the lowest level of erosion hazard. The determinant factors of soil erosion are plant management / vegetation and slope length/slope gradient. Conservation directions that can be carried out in Sidoharjo District for land use management improvement are a combination of vegetative conservation techniques such as the use of organic mulch and plant management to increase organic matter and mechanical conservation techniques such as terrace repairs to minimize soil loss.